INVESTIGATING THE PERCEIVED NEEDS OF INTERNATIONAL STUDENTS LEARNING EAP - Dedy Setiawan (TEFLIN, 2009)
Abstract: The perceived needs of students learning EAP were analysed u-sing a questionnaire which investigated the subjectsÃ¢â¬â¢ preference for particular topics and various modes of learning in relation to both the target and present situation. The target situation in the questionnaire was represented by items concerning study skills; while items concerning the present situation were oriented to the contents of the EAP course and its methodology and activities. The findings provide evidence for determining items for inclusion in an EAP programme. They also allow us to identify items as highly, reasonably or not at all recommended for inclusion.